Economic reforms in India and China : emerging issues and challenges - Sudhakara Reddy, B. (New Delhi, India : SAGE Publications India ; Thousand Oaks, Calif. : SAGE, 2009)
Papers presented at a conference held at Mumbai in February 2005.
Introduction, Economic reforms, Unanswered questions and open-ended answers / B. Sudhakara Reddy -- Political economy of post-1991 reforms / Suresh D. Tendulkar and T.A. Bhavani -- Institutional reform, trade and growth : the experiences of India and China in a global economy / Brigitte Desroches, Michael Francis and François Painchaud -- Impact of economic reforms and globalization on engineering education sector : a comparison of Indian and Chinese scenarios / N.J. Rao and K.G. Viswanadhan -- A comparative study of the implications of economic reforms on poverty in India and China / C. Ramasamy and K. Lokanadhan -- Financial system in India and China : a comparative study / Narendra Jadhav and Janak Raj -- Investment climate and productivity in Indian states / C. Veeramani and Bishwanath Goldar -- Export-led growth : characteristics contrasting India and China / Sebastian Morris -- China and India : what do their business firms have to say? / Rajalaxmi Kamath -- FDI flows in India and China / D. Krishnamoorthy -- Financial sector in China : issues and challenges / Surjit Singh -- Foreign direct investment : a comparative study of China and India / Anjali Kulkarni -- Myth and reality of FDI flows : Indian and Chinese integration with the global economy / Dolly Sunny -- Impact of China's access to WTO on FDI in Wuxi / Fu Xianzhi and Cai Jianying -- China's agriculture and WTO accession / Jatinder Bir Singh -- Impact of reforms on agricultural trade in India and China / Tulsi Lingareddy -- Regulation of employee inventions within patent law : a comparative overview of China and India / Rajesh Sagar and Aditya Nagarsheth -- Emerging challenges in pension policy : perspectives from China and India / Kumudini Hajra -- Prospects of ancient medical systems in India and China in today's world / Arijita Dutta -- Energy-environment linkages in India and China : a comparative review of issues and challenges / Ashir Mehta.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: India -- Economic conditions -- 1991-; India -- Economic policy -- 1991-2016.; China -- Economic conditions -- 2000-; China -- Economic policy -- 2000-; Inde -- Conditions économiques -- 1991-; Inde -- Politique économique -- 1991-2016.; Chine -- Conditions économiques -- 2000-; Chine -- Politique économique -- 2000-; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS -- Economics -- Comparative; BUSINESS & ECONOMICS -- Economic Conditions; BUSINESS & ECONOMICS -- Economic History; Economic history; Economic policy; China; India; Wirtschaftsreform; Indien; China; Wirtschaftsreform; Fiskalische Dezentralisierung; Direktinvestition; Finanzsektor; Agraraußenhandel; Indien; China; Since 1991